SUSTAINABLE DEVELOPMENT GOALS AS DOXA IN THE NETWORK PRACTICE OF ART COLLECTIVES IN INDONESIA - Azmi, Hidayatul (Universitas Gadjah Mada, 2025)
This study examine the phenomenon of networks of art collectives in Indonesia, which proliferated in the period leading up to 2020, and their connection to the global discourse of the Sustainable Development Goals. These networks represent a form of social practice that emerged from the transformation of the objective structure of the field of art and the subjective internalization of such changes by art practitioners. The research applies Pierre Bourdieu’s theory of social practice and employs a literature study method to map the social and economic relations of art collectives within the Indonesian art field from 2000 to 2024. By using Bourdieu’s framework, this study reveals that: (1) the structure of the artistic production field in Indonesia from 2000 to 2024 has been shaped by the art market and fund structures, which have driven the differing orientations of art collectives along two distinct heteronomous poles; (2) the network practices of visual art collectives in Indonesia are propelled by the discourse of sustainable development as a form of doxa produced by the field of power.